Price Characteristics at a Hay Auction. (1st March 2014) - McCullock, Katelyn; Davidson, Carolyn; Robb, James
Abstract : Hay is a major crop, though the market values are not often studied. The purpose of this research is to quantify relative price relationships due to a wide range of measurable hay characteristics of a specific hay auction reflecting supply and demand preferences. A time series data set was developed based on USDA Agricultural Marketing Service (AMS) reporting of the Colorado Centennial Hay Auction 2006 to 2011. All bale characteristics were gleaned from the reports including the number of tonnes offered at auction, hay type, grade, size, year, month, and the number of tonnes offered of a specific hay type, grade, size, year, and month combination. The data set was used to create a hedonic statistical price model for three hay types: alfalfa ( Medicago sativa L.), mixed alfalfa/grass, and grass hay. Time trend variables, grade, size, and the number of tonnes offered all proved to significantly impact price. The largest price increases were associated with specific grade size combinations, such as supreme quality small square bales. The biggest price reductions were associated with larger sized bales and lower quality grades. Alfalfa prices were the highest in this auction; the largest price variability was in grass hay. Results are largely applicable to a market area which includes buyers of hay for all types of livestock. Hay producers should carefully consider quality, type of hay (e.g., alfalfa), and bale characteristics in their production decisions.